2006
DOI: 10.1111/j.1439-0272.2006.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive infertility: changes in the histology of different regions of the epididymis and morphology of spermatozoa

Abstract: In the present study, the effects of prolonged obstruction in different regions of the human epididymis on its histology and on the spermatozoa retained at the site of obstruction were assessed. Men who were confirmed of having obstruction of the epididymis underwent vasoepididymostomy (VEA) for surgical correction of the obstruction. At the time of surgery, fluid from the epididymal tubule above the site of obstruction was aspirated and examined for sperm profile. Epididymal tissue, collected at the site of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Pal found that more motile sperm indicated better results. 13 In our study, the patency rate was significantly different if motile sperm was found (80.4% vs 25.0%). We also noticed more motile sperm in the epididymal fluid intraoperatively a better and higher VE patency rate could be predicted.…”
Section: Discussioncontrasting
confidence: 49%
“…Pal found that more motile sperm indicated better results. 13 In our study, the patency rate was significantly different if motile sperm was found (80.4% vs 25.0%). We also noticed more motile sperm in the epididymal fluid intraoperatively a better and higher VE patency rate could be predicted.…”
Section: Discussioncontrasting
confidence: 49%
“…However, development and function of the male reproductive tract, especially the cranial portion consisting of the efferent ductules (ducts), need appropriate activation of both the androgen and estrogen receptor pathways. In man, efferent ducts form the bulk of what is called the head or proximal part of the epididymis (Sullivan et al 2019; Légaré and Sullivan 2020) and pathological changes are more commonly found in this region in larger mammals, including obstructive lesions, which contribute substantially to male infertility (Ball and Mitchinson 1984;McEntee 1990;Rajalakshmi et al 1990; Pal et al 2006). The high incidence of epididymal disjunctions associated with epididymal anomalies points to the importance of understanding the endocrine regulation for development of the male ductal systems (Logsdon et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, obstructive lesions in the epididymis, especially in the proximal region, including the efferent ducts are not rare [ 1 ]. Patients with obstruction in the proximal region exhibit lower sperm motility and vitality than those with obstruction in the caudal region [ 34 ]. Therefore, it is important to understand what causes malformation and malfunction of the proximal region, including the efferent ducts.…”
Section: Introductionmentioning
confidence: 99%